Situation Report: Czechoslovakia, 23 November 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Political Terror: Contrasts in Condemnation Czech 'Pacem in Terris' Holds Congress Two Tests for the Civil Rights Movement CPCS Central Committee Plenum on Agriculture Czechoslovak Attitudes